Knowledge of Rabies Prevention in Vietnamese Public Health and Animal Health Workers. (20th February 2016) - Nguyen, K. A. T.; Nguyen, H. T. T.; Pham, T. N.; Van, K. D.; Hoang, T. V.; Olowokure, B.
Summary: Rabies is an invariably fatal, but preventable zoonotic disease. Despite a national programme for its prevention and control, the number of rabies associated deaths in Vietnam has increased in recent years. A cross‐sectional survey was undertaken in 2012 to assess and compare the knowledge, awareness and practices of 189 public health workers (PHW) and animal health workers (AHW) attending a joint training course for professionals from provinces in northern Vietnam with the highest number of deaths from rabies. Questionnaires facilitating self‐evaluation were provided, and total knowledge scores were calculated (maximum 38 points) and categorized into: 'high' (>30 points), 'moderate' (21–30) and 'low' (<21). The response rate was 100%, and among the 189 participants, 56% were PHW compared to 44% who were AHW. Although most respondents knew rabies could be transmitted through the bite of an animal, most commonly a dog, and that rabies is a preventable disease, significant differences between groups were identified. Major areas included poor knowledge of common rabies reservoirs, wound management and guidance on post‐exposure prophylaxis. Overall, the total mean knowledge scores for PHW was significantly higher ( P  = 0.011) compared to those for AHW, but both scores fell within the 'moderate' knowledge range. However, proportionately more PHW than AHW achieved 'high' knowledge scores ( P  = 0.0098). To our knowledge this is the first published study to simultaneously assess the knowledge and awareness of animal health and public health professionals attending joint training activities aimed at strengthening rabies prevention and control. To ensure effective prevention and control of rabies requires that AHW and PHW not only coordinate and collaborate, but have a common knowledge and understanding of rabies prevention and control measures. This study provides important baseline data in a relatively unexplored area of research that can focus future interventions and research.